2019
DOI: 10.20884/1.jdh.2019.19.1.2462
|View full text |Cite
|
Sign up to set email alerts
|

Prohibition of Intera Religion Marriage in Indonesia

Abstract: As a country with Pancasila as the philosophy, the first pillar is believing in God the One, therefore marriage is closely related to the issue of religion. Law number 1 in 1974 on Marriage stated that a marriage should be done by two people with the same religion and beliefs. Inter-religion marriage between Indonesian citizens in foreign states violate the regulations found in article 2 paragraph (1) and article 56 paragraph (1) of Law number 1 in 1974 on Marriage. The problems analyzed in this paper are: fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Inherently, Indonesia prohibits interfaith marriage, which can be seen from several religions' various rules and statements. However, this does not condemn the Indonesian people for carrying out interfaith marriages in various ways (Judiasih, Asrimayasha, & Sudini, 2019). Merely, interfaith marriages carry heavy social responsibilities: the couple must be ready to be ostracised by society (Çiğdem, 2015).…”
Section: The Regulation Of Interfaith Marriage In Indonesiamentioning
confidence: 99%
“…Inherently, Indonesia prohibits interfaith marriage, which can be seen from several religions' various rules and statements. However, this does not condemn the Indonesian people for carrying out interfaith marriages in various ways (Judiasih, Asrimayasha, & Sudini, 2019). Merely, interfaith marriages carry heavy social responsibilities: the couple must be ready to be ostracised by society (Çiğdem, 2015).…”
Section: The Regulation Of Interfaith Marriage In Indonesiamentioning
confidence: 99%
“…This is contained in Article 2 paragraph (1) of Law No. 1 of 1974 which reads (Judiasih, Nugraha, & Sudini, 2019):…”
Section: "The Inner and Outer Bond Between A Man And A Woman As Husba...mentioning
confidence: 99%
“…From the formulation of article 2 paragraph (1) of the marriage law, it can also be concluded that if a marriage is carried out not according to the laws of their respective religions and beliefs or if one of the marriage prohibitions is violated, then the marriage is invalid (Judiasih et al, 2019).…”
Section: "Marriage Is Valid If It Is Carried Out According To the Law...mentioning
confidence: 99%
“…As a result, interfaith marriage seemed problematic to be carried out in Indonesia. Actually, there was still an opportunity to do interfaith marriage in Indonesia by asking for a court order [1]. However, this method was not easy and required a relatively long time.…”
Section: Introductionmentioning
confidence: 99%